Sistem Pakar Diagnosis Penyakit Schizophrenia Menggunakan Metode Bayesian Network - Rima Diah Wardhani; Rekyan Regasari Mardi Putri; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Schizophrenia is a severe mental disorder that contains thoughts, language, perceptions, and self-awareness. There are several types of schizophrenia. The relationship between the type of schizophrenia and its symptoms has uncertainty, where a symptom A is not necessarily only result in schizophrenia type X, but can lead to schizophrenia type Y. In rural areas, mental health facilities are still inadequate, so that the people there treat patients with schizophrenia with unnatural as at the brackets even in stocks. Actually, people with schizophrenia can be handled with the provision of drugs and psychological therapy with regular. Based on these problems, the authors create expert systems that are able to find solutions as do an expert in diagnosing and providing treatment solutions in patients with schizophrenia. Thus, general practitioners in small community clinics or hospitals in small areas can diagnose patients suffering from the schizophrenia. This expert system uses Bayesian Network method, PHP programming language and MySQL database. Experimental functional test results show all functional requirements can run well. In addition, the highest accuracy test results in testing the variation of training data is 92.86%. With the results of such accuracy, this expert system has a good performance to make the diagnosis of schizophrenia disease